Development of TPACK-Based Digital Economics Worksheets to Enhance Students’ Critical Thinking Skills - Samakmur Samakmur; Sahlan Tuah; Ahmad Husein (Jurnal Paedagogy, 2026)
This study aims to develop TPACK-based digital economics worksheets and to examine their validity, practicality, and effectiveness in enhancing students’ critical thinking skills. The research employed a Research and Development (R&D) method using the ADDIE model, which consists of the analysis, design, development, implementation, and evaluation stages. The participants were tenth-grade students at SMK Negeri 1 Angkola Timur, North Sumatra. The research instruments included expert validation sheets, teacher and student response questionnaires, critical thinking skill tests, and learning achievement tests. Data were analyzed using descriptive quantitative and qualitative methods, normality testing, N-Gain analysis, and effectiveness testing. The findings revealed that the developed digital worksheets were highly valid based on evaluations by content, media, and instructional design experts. The practicality analysis indicated that the worksheets were highly practical, as reflected in positive responses from both teachers and students. Furthermore, the implementation of the TPACK-based digital worksheets was proven to be effective in improving students’ critical thinking skills, as demonstrated by increased mean scores and moderate to high N-Gain values. Therefore, TPACK-based digital economics worksheets are suitable for use as innovative instructional materials in vocational high school economics learning.